Implementation of Segmentation, Targeting and Positioning of Islamic Education Institutions - Dian Dian; Anggun Dewi; Wafiq Fadhilah Anwar; Muhamad Deden Jalaludin Sayuti (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2024)
Abstract MI Sunan Gunung Djati is a newly opened educational institution that requires a good and structured application of STP (Segmentation, targeting, positioning). In the first year of admission, 2021, it only got 35 students. Then in the second year of new student admissions, namely in 2022, the quota for Madrasah Ibtidaiyah students is 52 people, after carrying out a series of STP strategies, this quota set by MI is fulfilled. From here it can be seen that the STP strategy carried out succeeded in attracting potential consumers to use educational services at MI Sunan Gunung Djati. Seeing this phenomenon, researchers are interested in conducting research related to